Hydroxyanthracene derivates citotoxicity: A differential evaluation between single molecule and whole plant extract - Tinti, Laura; Cicaloni, Vittoria; Nezi, Paola; Isoldi, Giovanni; Etiope, Paolo; Barlozzini, Barbara; Pecorari, Rita; Salvini, Laura (Frontiers in Plant Science, 2023)
Hydroxyanthracene derivates (HADs) are a group of natural or synthetic compounds with a wide range of biological activities (for instance, anti-inflammatory, antibacterial, and antiarthritic). In addition, because of their properties for helping the normal bowel function, HADs are widely used in constipation as pharmacological drugs and nutritional supplements. Nevertheless, during the past years, a safety usage of HAD products has been under consideration because some studies reported that HADs are not lacking toxicity (i.e., genotoxic and carcinogenic activity). Thus, the first objective of this study is to shed light on the large variability in composition of botanical food supplements containing HAD by a systematic analysis of the qualitative and quantitative composition of a cohort of extracts and raw materials of plants with high levels of anthraquinones commercially available (Cassia angustifolia, Rhamnus purshiana, Rhamnus frangula, Rheum palmatum, and Rheum raponticum). To date, the investigation of HAD toxicity was based on in vitro and in vivo studies conducted mainly on the use of the single molecules (emodin, aloe-emodin, and rhein) rather than on the whole plant extract. The qualitative-quantitative characterization was the starting point to select the most appropriate products to be used as treatment for our in vitro cell studies. Thus, the second objective of this study is the investigation, for the first time, of the toxic events of HAD used as single molecule in comparison with the whole plant extracts containing HAD in an intestinal in vitro model using human colorectal adenocarcinoma cells (Caco-2). In addition, a shotgun proteomics approach was applied to profile the differential protein expression in the Caco-2 cells after a single-HAD or whole–plant extract treatment to fully understand the potential targets and signaling pathways. In conclusion, the combination of a detailed phytochemical characterization of HAD products and a largely accurate analysis of the proteomic profile of intestinal cells treated with HAD products provided the opportunity to investigate their effects in the intestinal system.